Necrobiosis lipoidica in a 7-year-old non-diabetic boy. - Hannert, H.P.; Fritz, A.; Kaddu, S.; Müllegger, R. (European Journal of Pediatric Dermatology, 2023)
Necrobiosis lipoidica (NL) is a rare granulomatous skin disease of unknown origin that usually occurs in adults and requires long-term treatment. Here was reported a 7-year-old boy with histopathologically proven necrobiosis lipoidica (NL) on his lower back. He was successfully treated with intralesional and topical corticosteroids and tacrolimus ointment. This case is remarkable for its age of onset, location on the trunk, and absence of diabetes mellitus, which usually is significantly associated with the rare cases of NL in children.